Perlindungan Hukum terhadap Anak Korban Eksploitasi Ekonomi di Kota Makassar: Telaah Undang-Undang Perlindungan Anak dan Hukum Islam - Ismail, Khumaerah; Syamsuddin, Rahman; Irfan, Irfan (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to examine the forms of child exploitation that occur in Makassar City, an analysis of regulations in Law Number 35 of 2014, as well as the views of Islamic law on the protection of child victims of exploitation. The method used is qualitative with data collection techniques through interviews, observations, documentation, and literature studies. The results of the study show that forms of child exploitation in Makassar include buskers, beggars, street vendors, and children in costumes. The main driving factor is economic problems. Many families depend on their children's activities on the street for their livelihoods. The government, through the social service, seeks to minimize this phenomenon with monthly assistance to poor families. Regulatively, Article 76I Jo Article 88 of Law No. 35 of 2014 prohibits economic and sexual exploitation of children, with a maximum penalty of 10 years in prison and/or a fine of up to Rp200 million. However, many cases do not proceed to legal proceedings due to a lack of evidence. Therefore, the restorative justice approach is considered more effective. In an Islamic perspective, child exploitation is contrary to the principles of Maqasid al-Sharia, which emphasizes the importance of safeguarding and protecting future generations. MUI Fatwa Number 1 of 2021 also emphasizes that the practice of begging involving children is classified as exploitation and unlawful. The implications of this study emphasize the importance of the role of the community and the government in increasing public awareness through education, seminars, social media campaigns, and stricter law enforcement for the protection of children's rights.